Li/Mg systematics in scleractinian corals: Calibration of the thermometer - Montagna, Paolo; McCulloch, Malcolm; Douville, Eric; Correa, Matthias López; Trotter, Julie; Rodolfo-Metalpa, Riccardo; Dissard, Delphine; Ferrier-Pagès, Christine; Frank, Norbert; Freiwald, André; Goldstein, Steve; Mazzoli, Claudio; et al. (2014)
We show that the Li/Mg systematics of a large suite of aragonitic coral skeletons, representing a wide range of species inhabiting disparate environments, provides a robust proxy for ambient seawater temperature. The corals encompass both zooxanthellate and azooxanthellate species ( Acropora sp., Porites sp., Cladocora caespitosa , Lophelia pertusa , Madrepora oculata and Flabellum impensum ) collected from shallow, intermediate, and deep-water habitats, as well as specimens cultured in tanks under temperature-controlled conditions. The Li/Mg ratios observed in corals from these diverse tropical, temperate, and deep-water environments are shown to be highly correlated with temperature, giving an exponential temperature relationship of: Li/Mg (mmol/mol) = 5.41 exp (−0.049 * T ) ( r ² = 0.975, n = 49). Based on the standard error of the Li/Mg versus temperature correlation, we obtain a typical precision of ±0.9 °C for the wide range of species analysed, similar or better than that of other less robust coral temperature proxies such as Sr/Ca ratios.The robustness and species independent character of the Li/Mg temperature proxy is shown to be the result of the normalization of Li to Mg, effectively eliminating the precipitation efficiency component such that temperature remains as the main controller of coral Li/Mg compositions. This is inferred from analysis of corresponding Li/Ca and Mg/Ca ratios with both ratios showing strong microstructure-related co-variations between the fibrous aragonite and centres of calcification, a characteristic that we attribute to varying physiological controls on growth rate. Furthermore, Li/Ca ratios show an offset between more rapidly growing zooxanthellate and azooxanthellate corals, and hence only an approximately inverse relationship to seawater temperature. Mg/Ca ratios show very strong physiological controls on growth rate but no significant dependence with temperature, except possibly for Acropora sp. and Porites sp. A strong positive correlation is nevertheless found between ...